Essentials of early English an introduction to Old, Middle, and Early Modern English - Smith, J. J. 1955- (Routledge, Taylor & Francis Group, 2023)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- Part I Description -- 1 Introduction -- 1.1 About this Book -- 1.2 English and Its Origins -- 1.3 External History -- 1.4 Internal History -- 1.5 Introducing English Historical Linguistics -- 1.6 A Preliminary Illustration -- Old English (West Saxon, Late Ninth Century) -- Middle English (Kentish, 1340) -- Middle English (Central Midlands, C. 1380) -- Older Scots (C. 1520) -- Early Modern English (Book of Common Prayer, 1549) -- Present-Day English (Alternative Service Book) -- 2 Describing Language -- 2.1 Introduction -- 2.2 The Levels of Language -- 2.3 Speech and Writing -- 2.4 Phonetics and Phonology -- 2.4.1 Vowels -- 2.4.2 Consonants -- 2.4.3 Syllables -- 2.5 Grammar and Lexicon -- 2.5.1 The Hierarchy of Grammatical Units -- 2.5.2 Morphemes -- 2.5.3 Words -- 2.5.4 Phrases -- Phrases: Forms -- Phrases: Functions -- Subordinate Phrases -- 2.5.5 Clauses -- 2.5.6 Some Further Grammatical Categories -- Noun Phrase Categories -- Verb Phrase Categories -- 3 Old English -- 3.1 Introduction -- 3.2 Spelling and Pronunciation -- 3.2.1 The Alphabet -- 3.2.2 Diacritics -- 3.2.3 Pronunciation -- 3.3 Syntax -- 3.3.1 The Noun Phrase -- Case and the Noun Phrase -- Agreement and the Noun Phrase -- Number, Gender, and the Noun Phrase -- The Noun Phrase: Pronouns -- The Noun Phrase: Adjectives -- The Noun Phrase: Determiners -- The Noun Phrase: Numerals -- The Noun Phrase: a Note About Genitive Phrases -- The Noun Phrase: a Note About Prepositional Phrases -- 3.3.2 The Verb Phrase -- Agreement and the Verb Phrase -- Finite and Non-Finite Verbs and the Verb Phrase -- Simple and Complex Verb Phrases -- Number and the Simple Verb Phrase -- Person and the Simple Verb Phrase -- Tense and the Simple Verb Phrase -- Mood and the Verb Phrase.
Keywords: Geschichte 700-1600; Geschichte Anfänge-1678; Mittelenglisch; Historische Grammatik; Grammatik; Altenglisch; Englisch; Frühneuenglisch; Anthologie; Einführung